Accelerated transepithelial corneal cross-linking for progressive keratoconus: a prospective study of 12 months. Issue 9 (5th January 2017) - Aixinjueluo, Wei; Usui, Tomohiko; Miyai, Takashi; Toyono, Tetsuya; Sakisaka, Toshihiro; Yamagami, Satoru
Abstract : Background/aims: To evaluate the clinical results of accelerated transepithelial corneal cross-linking (CXL) in Japanese patients with progressive keratoconus (KCN). Methods: Thirty eyes of 19 patients (16 male, 3 female patients) with progressive KCN were included. The mean age was 24.9±7.0 (range 16–38) years. All patients received ultraviolet A radiation for 3 min at an irradiance of 30 mW/cm 2 . Patients were followed up on the first day, at 1 week and 2 weeks, and at 1 month, 3 months, 6 months and 12 months postoperatively. Clinical examinations included measures of uncorrected visual acuity, best corrected visual acuity (BCVA), average keratometry (AveK), maximum keratometry (Kmax), central corneal thickness, thinnest corneal thickness (TCT), endothelial cell density, intraocular pressure and non-mydriatic indirect fundus examination. Patients were asked to report any pain or discomfort at each visit. Results: There were no intraoperative or postoperative complications. All 30 eyes finished the follow-up. After 12 months, there was a significant decrease in Kmax (p<0.0001), AveK (p=0.003) and TCT (p=0.002), and a significant improvement in BCVA (p=0.001). There were no other significant changes. Pain or foreign-body sensation following CXL appeared in the first 2 days, but lasted no more than 1 week in all cases. Conclusions: There were no complications associated with accelerated transepithelial corneal CXL, and the clinical outcomes were appraisable in a 12-month follow-up. Trial registration number: UMIN000009372.